Association between the position of impacted third molars and external root resorption of adjacent second molars observed through cone-beam computed tomography - Atuncar Salazar, Jenny Teresa (2025)
Objective: To determine the association between the position of impacted third molars and root resorption of adjacent second molars observed through cone-beam computed tomography in patients who attended a dental teaching center in Lima, Peru. Materials and methods: A cross-sectional, retrospective, and observational study was conducted on 84 cone-beam computed tomography (CBCT) scans that met the selection criteria, evaluating 153 impacted third molars according to Winter’s classification and their respective adjacent second molars. Results: Impacted third molars were found predominantly among women (57.1%; n = 48) and in patients aged 16 to 25 (59.5%; n = 50), with a predominance of the mesioangular position (77.8%; n = 119) and mandibular location (81.0%; n = 124). External root resorption of the second molar was observed in 13.1% (n = 20) of the total cases, mostly in women (70.0%; n = 14) and in patients aged 16 to 25 (60.0%; n = 12). The most frequent location was the cervical third (60.0%; n = 12), and the degree of resorption was mostly mild (80.0%; n = 16). A statistically significant association was observed between impacted third molars and external root resorption of the adjacent second molar (p < 0.001), as well as between the latter and the position of the impacted third molar (p = 0.002). Conclusions: There is an association between the position of the impacted third molar and root resorption of adjacent second molars, with the mesioangular position presenting the highest risk.